Patellar Proximo-Distal Displacement following Modified Maquet Technique Is Not Predictive of Patellar Luxation - Giansetto, Thomas Elie; Pierrot, Emilie; Picavet, Pierre P.; Lefebvre, Michael; Rives, Albane; Farnir, Frédéric; Claeys, Stéphanie; Balligand, Marc (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to test the low sensitivity of the Allberg and Miles index to the stifle opening angle, evaluate the displacement of the patella after a Modified Maquet Technique using this index and assess the incidence of patellar luxation post-Modified Maquet Technique in dogs.Study Design Medical records were reviewed from 2012 to 2017. Allberg Miles index were determined for each stifle pre- and postoperatively, as well as the stifle joint opening of each case. Occurrence of patellar luxation was recorded.Results 137 stifles on 116 dogs were reviewed. The stifle opening angle did not influence the Allberg Miles index. Pre- and postoperative index showed a distal displacement of the patella after a Modified Maquet Procedure, especially at 135° of stifle opening angle. Only 1/137 cases demonstrated patellar luxation after the surgery.Conclusion Based on our statistical analysis, we were able to conclude that within the maximum stifle opening angle range recorded in our series of cases; the Allberg Miles index variation was not significant. While patellar baja is clearly induced by the Modified Maquet Technique, the latter did not seem to predispose patients to post-operative patellar luxation in our study population.
Keywords: Modified Maquet Technique; Cranial Cruciate Ligament Disease; dogs; patellar luxation; patellar baja